Prerequisite Evaluation of Anaerobic Settings for Gut Microbiome Functional Studies - Muhammad Nur `Adam Hatta; Ezanee Azlina Mohamad Hanif; Siok-Fong Chin; Hui-min Neoh (Faculty of Medicine, Diponegoro University, 2021)
Colon cancer-associated gut bacteria were mostly identified via next-generation sequencing in gut microbiome profiling studies. Anaerobic culture systems can be used to culture colon cells with these gut bacteria to further confirm the tumorigenic properties of these bacteria. Nevertheless, it is unclear how colon cells will grow in an anaerobic environment, as most cells are cultured aerobically. Therefore, we investigated the survival and viability of HT-29, a colon cancer cell line in an anaerobic culture system, and compared it to the usual culture condition in an aerobic setup. Interestingly, we found that HT-29 was able to grow in the anaerobic setup. Its viability was similar for both culture conditions, with only a slower growth rate observed in the anaerobic setup. Furthermore, gene expression studies showed that the cells were not under severe anaerobic stress even when exposed to the oxygen-deprived environment.This study provided results on some baseline parameters of an anaerobic colon cell culture system, and will be useful for journal readers who wish to investigate functional properties of anaerobic bacteria.